Analyzing Pacemaker Leads: Application of a Form of Energy - Menard, Mariane; Tyndall, Judi (Operating Room Nurses Association of Canada Journal, 2000)
In the province of Ontario, analyzing of pacemaker leads is a delegated controlled act. This article describes the certification/recertification process for analyzing of pacemaker leads at the Hamilton Health Sciences Corporation.